MANAJEMEN STRATEGIK PEMBERDAYAAN ORANG TUA/WALI MURID - Subiyanto, Subiyanto (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2009)
The relationship between school and society basically is a tool that are crucial in encouraging growth in developing participants strudents in the social system as is more likely to achieve an effective educational and community efisien.